Reflections on Comparing Basic Education Systems in Indonesia: Analysis of Curricula and Learning Approaches in Elementary Schools - Moch Mukhlison; Ari Susetiyo (Lembaga Pendidikan Hikmatun Najah Blora, 2025)
Elementary education in Indonesia is characterized by diversity in approaches and curricula, influenced by social, cultural, and religious contexts. This study aims to compare the elementary education systems of public elementary schools, Islamic elementary schools, and Madrasah Ibtidaiyah, focusing on curriculum and teaching methods. Public elementary schools follow the 2013 National Curriculum and the Merdeka Curriculum, emphasizing competency-based learning and a scientific approach, while Islamic elementary schools integrate Islamic values into these curricula, and Madrasah Ibtidaiyah highlights formal religious content as the core of education. This study employs a literature review method to analyze the structural differences and pedagogical approaches across the three school types. Findings reveal that, despite shared basic structures, significant differences exist in the prioritization of religious content, teaching methods, and curriculum flexibility. The discussion underscores the implications of these differences for character development and the relevance of education in the modern era. This research concludes with a call for curriculum harmonization that supports pluralism and pedagogical innovation to enhance the quality of elementary education in Indonesia.